Results of Work of the Specialized Anti-Epidemic Teams of the Irkutsk Research Anti-Plague Institute in the Amur Region, Khabarovsk Territory and the Jewish Autonomous Region in 2013 - S. V. Balakhonov; S. A. Kosilko; A. K. Noskov; L. M. Mikhailov; M. V. Chesnokova; E. S. Kulikalova; V. A. Vishnyakov; N. V. Breneva; N. G. Gefan (Проблемы особо опасных инфекций, 2014)
Displayed are the major results of work of the specialized anti-epidemic teams from Irkutsk Research Anti-Plague Institute, aimed at the provision for sanitary-epidemiological welfare of the population in the Amur Region, Khabarovsk Territory and the Jewish Autonomous Region, devastated by the abnormally high water, in 2013. Represented are the data on sanitary-hygienic and epidemiological monitoring over the territory of the worst-hit areas. Revealed are the findings as regards examination of water samples obtained from the centralized and decentralized water supplies, surface water reservoirs and treatment facilities for presence of Vibrio cholerae , and of clinical material - for intestinal viruses, as well as serological screening of the decreed groups and foreign citizens temporarily working in the Russian Federation. Presented are the results of epizootiological-epidemiological inspection of the endemic areas for natural-focal infections, and also potentially hazardous areas as concerns anthrax, situated within the bonds of the flooded territories. Total of 3626 samples have been tested, 15502 analyses for 23 nosological entities have been performed.